2022
DOI: 10.3390/ma15072405
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Properties of Micronized Natural Zeolitic Volcanic Tuff as Cosmetic Ingredient

Abstract: This study explores the characteristics of a micronized natural zeolitic volcanic tuff (MZ) as ingredient in cosmetic formulations. In particular, the purpose was to prepare and investigate the organoleptic and physicochemical properties of two representative cosmetic formulations containing MZ. The MZ samples were characterized using X-ray fluorescence (XRF), X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) spectroscopy. pH, cation exchange capacity (CEC), apparent density, chemical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The concentrations of As, Cd and Co were below LOQs, while the concentrations of other elements in NZ100 and NZ40 samples were 3.43 and 3.09 mg kg −1 Cr, 9.47 and 9.23 mg kg −1 Cu, 3.31 and 3.45 mg kg −1 Ni, 7.11 and 6.36 mg kg −1 Pb, and 20.4 and 22.9 mg kg −1 Zn ( Table 3 ). Metal concentrations in the same order of magnitude were reported for Romanian natural zeolites from Racosu de Jos deposit (7.31–8.70 mg kg −1 Cr, 1.65–2.03 mg kg −1 Cu, 3.21–4.35 mg kg −1 Ni, 4.69–6.78 mg kg −1 Pb, 4.08 and 4.41 mg kg −1 Zn, and <1 mg kg −1 Cd [ 42 ] and different deposits (<1–11.1 mg kg −1 Cr, 7.9–27.9 mg kg −1 Cu, 2.1 and 10.7 mg kg −1 Ni, <1–28.5 mg kg −1 Pb, and 14 and 64.1 mg kg −1 Zn [ 43 ]. However, Tomasevic-Canovic [ 44 ] reported 29–38 mg kg −1 Pb, 240–305 mg kg −1 Mn, 40–305 mg kg −1 Zn for natural zeolites from Serbia and Montenegro and highlighted the necessity of testing heavy metals bioavailability in zeolites when used for human.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of As, Cd and Co were below LOQs, while the concentrations of other elements in NZ100 and NZ40 samples were 3.43 and 3.09 mg kg −1 Cr, 9.47 and 9.23 mg kg −1 Cu, 3.31 and 3.45 mg kg −1 Ni, 7.11 and 6.36 mg kg −1 Pb, and 20.4 and 22.9 mg kg −1 Zn ( Table 3 ). Metal concentrations in the same order of magnitude were reported for Romanian natural zeolites from Racosu de Jos deposit (7.31–8.70 mg kg −1 Cr, 1.65–2.03 mg kg −1 Cu, 3.21–4.35 mg kg −1 Ni, 4.69–6.78 mg kg −1 Pb, 4.08 and 4.41 mg kg −1 Zn, and <1 mg kg −1 Cd [ 42 ] and different deposits (<1–11.1 mg kg −1 Cr, 7.9–27.9 mg kg −1 Cu, 2.1 and 10.7 mg kg −1 Ni, <1–28.5 mg kg −1 Pb, and 14 and 64.1 mg kg −1 Zn [ 43 ]. However, Tomasevic-Canovic [ 44 ] reported 29–38 mg kg −1 Pb, 240–305 mg kg −1 Mn, 40–305 mg kg −1 Zn for natural zeolites from Serbia and Montenegro and highlighted the necessity of testing heavy metals bioavailability in zeolites when used for human.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, after alginate coating, calcium deposition increased in both 7 and 14 days. Similarly, various studies [68][69][70][71][72][73][74][75][76][77][78][79][80] reported that alginate coating increased calcium deposition and new bone formation. For example, Jang et al [69] demonstrated the great calcium deposition results on the PCL scaffold with alginate coating.…”
Section: In Vitro Cytocompatibility Of Scaffoldsmentioning
confidence: 91%